MEMINIMALISIR STEREOTIPE ANTAR GENDER DENGAN MENGGUNAKAN TEKNIK UNGKAP TANGKAP CURAHAN HATI PADA MATERI DIFERENSIASI SOSIAL DI SMA CENDANA PEKANBARU - Bambang Kariyawan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
Various policies have been made to achieve gender equality still encountering many obstacles. The biggest obstacle lies in the understanding of the perception that men are superior and women identical to inferior. In other words, there is still a stereotype perception that is difficult to be shifted to establish gender equality. Similarly to the learning process in the classroom can not be separated from issues of gender. This condition can be anticipated by applying learning through the process of in-depth dialogue between genders using reveal-capture-effusive techniques. This study was conducted to determine the learning steps using reveal-capture-effusive techniques on social differentiation material and to determine the effect given from the learning process by using the reveal-capture-effusive techniques to minimizing gender stereotypes in the classroom. Learning undertaken consisting of measures in the form of a dialogue with each other and express their own gender advantages and assess the other gender advantages, gender case analysis and dialogue through the mass media, cases of gender analysis and dialogue in daily life, and gender dialogue with gender experts. By using the approach of classroom action research (PTK) with two cycles and research instruments such as observation, field notes, and tests found the results of research that learning by using reveal-capture-effusive techniques can minimize stereotypes between gender groups of male students and female students and increase students’ test results. Observations in the classroom to the indicator of the ability of students to listen to opposing gender argued a number of 12 students (43%) are in a good range in cycle 1 increased to 24 students (86%) in cycle 2. For indicator positive response to expressions of gender opponent shows that the number of 8 students (29%) are in a good range in the first cycle and increased to 22 students (79%) in second cycle. The results of written tests conducted in each cycle showed an increase from an average of 76.5 to an average of 80.1. Implementation of the reveal-capture-effusive techniques can be an alternative out pouring of learning that can appreciate the differences in the group through the process of in-depth dialogue.